2020
DOI: 10.11124/jbisrir-d-19-00170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout among nurses in sub-Saharan Africa: a systematic review

Abstract: Convert the Z scores to t-scores with raw score mean = 50 and the raw score standard deviation = 10, if this is something you wish to do within your own sample. SPSS code is provided for this below. COMMENT: Step 1: Score ProQOL IV. or 5 Variable names in syntax assume pq# for each item. This routine reverses items 1,14,15, 17 and 29 then scores the three scales of the ProQOL IV; Secondary Traumatic Stress the new scale name for the old Compassion Fatigue scale. RECODE pq1 pq4 pq15 pq17 pq29 (1=5) (2=4) (3=3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 48 publications
3
35
3
Order By: Relevance
“…It is also comparable with the study conducted in Iran; the overall prevalence of burnout among Iranian nurses was 36% [ 30 ]. Similarly, our finding was also consistent with the study done in sub-Saharan Africa which was 33% [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is also comparable with the study conducted in Iran; the overall prevalence of burnout among Iranian nurses was 36% [ 30 ]. Similarly, our finding was also consistent with the study done in sub-Saharan Africa which was 33% [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…The sub-Saharan African region had the highest burnout symptom prevalence rate while Europe and Central Asia region had the lowest [ 7 ]. A systematic review conducted in sub-Saharan Africa showed that the prevalence of burnout among nurses was 33% [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta‐analyses have already shown that nurses present moderate to high levels of burnout syndromes (Adriaenssens et al, 2015; De la Fuente‐Solana et al, 2019; Gómez‐Urquiza et al, 2016; López‐López et al, 2019; Owuor et al, 2020; Pradas‐Hernández et al, 2018; Woo et al, 2020). The prevalence of burnout syndromes is different between geographical regions and specialties.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of burnout syndromes is different between geographical regions and specialties. In particular, Central Asia and Europe had the lowest burnout symptoms prevalence, while the Sub‐Saharan Africa region had the highest (Owuor et al, 2020; Woo et al, 2020). Also, paediatric, oncology and emergency nurses had the highest burnout symptoms prevalence (Gómez‐Urquiza et al, 2016, 2017; Parola et al, 2017; Pradas‐Hernández et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…8 In a systematic review of 12 studies from seven African countries, using the Maslach Burnout Inventory, the prevalence of emotional exhaustion was 66%, depersonalization was 37%, and low personal achievement was 49%. 9 Several studies have been carried out on burnout among nurses in Nigeria. For example, in a study carried out in a General Hospital in Oyo state, 39.1% of the respondents had burnout in the area of emotional exhaustion, 29.2% in the area of depersonalization and 40.0% in the area of reduced personal accomplishment.…”
Section: Introductionmentioning
confidence: 99%